Firing-Associated Recycling of Coal-Fired Power Plant Fly Ash - Vu Thi Ngoc Minh; Vuong-Hung Pham; Vu Hoang Tung; Cao Tho Tung; Nguyen Thi Hong Phuong (Journal of Analytical Methods in Chemistry)
Coal-fired power plant fly ash is a global environmental concern due to its small particle size, heavy metal content, and increased emissions. Although widely used in concrete, geopolymer, and fly ash brick production, a large amount of fly ash remains in storage sites or is used in landfills due to inadequate raw material quality, resulting in a waste of a recoverable resource. Therefore, the ongoing need is to develop new methods for recycling fly ash. The present review differentiates the physiochemical properties of fly ash from two coal combustion processes: fluidized bed combustion and pulverized coal combustion. It then discusses applications that can consume fly ash without strict chemical requirements, focusing on firing-associated methods. Finally, the challenges and opportunities of fly ash recycling are discussed.